Interferon-induced activation of dendritic cells and monocytes by yellow fever vaccination correlates with early antibody responses - Elena Winheim; Antonio Santos-Peral; Tamara Ehm; Linus Rinke; Sandra Riemer; Magdalena Zaucha; Sebastian Goresch; Lisa Lehmann; Katharina Eisenächer; Michael Pritsch; Giovanna Barba-Spaeth; Tobias Straub; et al. (Proceedings of the National Academy of Sciences, 2025)
Yellow fever vaccination provides long-lasting protection and is a unique model for studying the immune response to an acute RNA virus infection in humans. To elucidate the early innate immune events preceding the rapid generation of protective immunity, we performed transcriptome analysis of human blood dendritic cell (DC) and monocyte subpopulations before and 3, 7, 14, and 28 d after vaccination. We detected temporary upregulation of IFN-stimulated genes (ISG) in all DC and monocyte subsets on days 3 and 7 after vaccination as well as cell type–specific responses and response kinetics. Single-cell RNA sequencing revealed rapid appearance of activated DC and monocyte clusters dominated by ISGs, inflammatory chemokines, and genes involved in antigen processing and presentation. This was confirmed by flow cytometric analysis in a large cohort of vaccinees. We identified SIGLEC1/CD169 upregulation as a sensitive indicator of the transient IFN-induced activation state elicited in DCs and monocytes by YF17D vaccination correlating with early protective IgM antibody responses.